2022
DOI: 10.1002/anie.202206233
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Proton‐Feeding Effect in Sulfur‐Doped Fe−N−C Single‐Atom Catalyst for Enhanced CO2 Electroreduction

Abstract: Heteroatom-doping in metal-nitrogen-carbon single-atom catalysts (SACs) is considered a powerful strategy to promote the electrocatalytic CO 2 reduction reaction (CO 2 RR), but the origin of enhanced catalytic activity is still elusive. Here, we disclose that sulfur doping induces an obvious proton-feeding effect for CO 2 RR. The model SAC catalyst with sulfur doping in the second-shell of FeN 4 (Fe 1 À NSC) was verified by Xray absorption spectroscopy and aberration-corrected scanning transmission electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
159
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(163 citation statements)
references
References 66 publications
4
159
0
Order By: Relevance
“…Generally, it is considered that feeding sufficient protons is a prerequisite for the formation of CH 3 OH because it can facilitate the activation of CO 2 and match the requirement of the 4-proton transfer reaction. [31][32][33][34][35][36] However, it is noteworthy that the content of protons generated often exhibits a positive correlation with the concentration of strongly oxidizing species generated owing to the sluggish reaction kinetics in the photocatalytic H 2 O oxidation process. 4,15,37,38 Thus, based on the above-mentioned considerations, solving this dilemma is highly required for achieving the selective photocatalytic reduction of CO 2 to CH 3 OH with high activity but a huge challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, it is considered that feeding sufficient protons is a prerequisite for the formation of CH 3 OH because it can facilitate the activation of CO 2 and match the requirement of the 4-proton transfer reaction. [31][32][33][34][35][36] However, it is noteworthy that the content of protons generated often exhibits a positive correlation with the concentration of strongly oxidizing species generated owing to the sluggish reaction kinetics in the photocatalytic H 2 O oxidation process. 4,15,37,38 Thus, based on the above-mentioned considerations, solving this dilemma is highly required for achieving the selective photocatalytic reduction of CO 2 to CH 3 OH with high activity but a huge challenge.…”
Section: Introductionmentioning
confidence: 99%
“…To unravel the reaction mechanism, we investigated both the H 2 O activation and hydrogen bond interaction which are proposed to be important for the HER and CO 2 RR. 50,51 We found that, for single molecule adsorption, the adsorption of H 2 O over a Co site is much stronger (adsorption energy E ads = −1.23 eV) than that of CO 2 ( E ads = −0.25 eV), indicating a preference towards H 2 evolution rather than the CO 2 RR under a low H 2 O content (Fig. S20†).…”
Section: Resultsmentioning
confidence: 95%
“…The binding energy of Fe 2+ and Fe 3+ doublets in FeS/FeNSC exhibits a negative shift by ≈0.5 eV relative to FeNC, which implies FeS nanoparticles and oxidized sulfur functionalities synergistically inducing an electron-rich structure of Fe. [54,55] In order to investigate the coordination and chemical information of Fe in FeS/FeNSC, X-ray adsorption fine structure (XAFS) spectroscopy was performed. Fe X-ray absorption near edge structure (XANES) spectrum (Figure 3a) displays that the edge position of FeS/FeNSC is located between FeO and Fe foil, indicating the valence state for Fe is between 0 and +2.…”
Section: Resultsmentioning
confidence: 99%